Decision Support System for Selection of Scholarship Awardees and Residents of Nusantara Surabaya Student Dormitory - Chrystia Aji Putra; Made Hanindia Prami Swari; Rahmawati F. Tias; Maurisa Arimbi Putri (Jurnal Info Sains : Informatika dan Sains, 2023)
Nusantara Student Dormitory (AMN) is a scholarship and boarding program intended for the nation's best children. The program has a rigorous selection to ensure that only the best candidates get the scholarship. However, the manual selection process can slow down the announcement of the graduation of the admission selection. This research aims to build a Decision Support System (DSS) to assess AMN scholarship candidates. The SPK was built using a combined method between AHP and Topsis. The results showed that the SPK built can provide quite good results. The system can provide ranking results in accordance with the criteria, namely academic ability in the form of report cards, ideological mental conditions, achievements, interests, health, personality, and color blindness test results. The system has also been tested and shows consistent results. Based on the results of the study, it can be concluded that SPK can be used to provide decisions on scholarship awardees and residents of AMN Surabaya.